1999
DOI: 10.1038/sj.ijo.0800886
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, obesity and blood lipids

Abstract: PURPOSE: To present the evidence concerning the in¯uence of physical activity on the dyslipidaemia of obesity and overweight. METHODS: Review of a personal library of literature on the interactions of physical activity, lipoprotein metabolism and body fatness. SUMMARY OF FINDINGS: Obesity, in particular abdominal obesity, is associated with dyslipidaemia Ð speci®cally elevated plasma concentrations of triacylglycerol (TAG) in the fasted state, an exaggerated postprandial rise in plasma TAG, low concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
8

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 61 publications
1
33
0
8
Order By: Relevance
“…In adults both physical activity and aerobic ®tness are associated with healthy lipid pro®les and these relationships may be mediated, in part, through body fatness. 20 Whether these ®ndings are applicable to children is uncertain. There is evidence that obese children are less active than non-obese children and that they have a lower aerobic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In adults both physical activity and aerobic ®tness are associated with healthy lipid pro®les and these relationships may be mediated, in part, through body fatness. 20 Whether these ®ndings are applicable to children is uncertain. There is evidence that obese children are less active than non-obese children and that they have a lower aerobic capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is suggested that the exacerbated increase in the lipolysis rate results in high concentrations of nonesterified fatty acids, contributing to increased hepatic synthesis of VLDL. Besides, it inhibits glucose uptake stimulated by insulin, in a dose-dependent way, resulting in insulin resistance 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A ingestão aumentada de lipídeos pode levar ao aparecimento de obesidade, diabetes tipo 2 e doenças cardiovasculares 6 . Em face do exposto, neste estudo verificamos as alterações provocadas por uma dieta hiperlipídica palatável, administrada a ratos por período prolongado.…”
Section: N T R O D U ç ã Ounclassified